Green Accounting and Sustainable Corporate Performance: Environmental Performance as a Moderating Variable - Christy, Yunita; Tjun, Lauw Tjun (Universitas Pendidikan Indonesia, 2024)
This study aims to investigate whether sustainable corporate performance is influenced by green accounting practice and analyze environmental performance position as a moderating variable in this relationship. Cross-sectional time-series analysis together with random effects regression model was deployed for data analysis. The findings indicate that green accounting, proxied by environmental costs, negatively affects sustainable corporate performance, where greater efficiency in environmental cost components for green accounting activities positively impacts sustainable corporate performance (ROE). However, not significant moderation effect of environmental performance observes in the relationship betwixt green accounting and sustainable corporate performance. Companies that increase environmental costs to enhance compliance and achieve higher PROPER ratings experience a decline in ROE. Theoretically, vision given from this study regarding the importance of environmental cost efficiency in green accounting practices to support sustainable corporate performance. Practically, it suggests that companies should integrate environmental aspects comprehensively into their business strategies and effectively implement sustainable practices to achieve optimal corporate performance. Compared to previous research, this research uses environmental performance as a moderating variable, which has not been previously explored in the relationship betwixt green accounting and sustainable corporate performance and this become novelty of this research.